Cultural Nationalism in Colonial Korea, 1920-1925 - Robinson, Michael Edson (Book collections on Project MUSE., 2014)
"By studying the early splits within Korean nationalism, Michael Robinson shows that the issues faced by Korean nationalists during the Japanese colonial period were complex and enduring. In doing so, Robinson, in this classic text, provides a new context with which to analyze the difficult issues of political identity and national unity that remain central to contemporary Korean politics; Michael Edson Robinson is professor of East Asian languages and cultures at Indiana University; "Robinson's study helps us understand the climate that developed in Korea under the Japanese and why, after liberation, the Koreans themselves seemed to split so readily along cold war lines"--American Historical Review; "The book is valuable enough because it provides a background to contemporary or recent events. More than this, though, it is invaluable since it provides an unbiased dissection of a five-year-long intellectual movement. It should be essential reading for anyone concerned with Korean history"--Bulletin of the School of Oriental and African Studies"--